Garden Warden: Garden Watering Automation System to Maintain Soil Moisture Based on IoT (Internet of Things) - Zata Ismah Sumayyah; Divo Wibowo Adi; Muhammad Fathurrahman; Muhammad Karim Bachtiar; Muhammad Rafid Habibi; Muhammad Tsabit; Ramma Dwi Rachmat; Sista Naelly Adzimi; Stephen Nathaniel (Batrisya Education, 2025)
Water requirements are an important factor in plant growth. Manual watering systems are often ineffective and time consuming. IoT-based garden watering automation systems can be a solution to overcome these problems. The Internet of Things (IoT)-based garden watering automation system uses soil moisture sensors and integrates with telegram chat applications that have been developed to maintain soil moisture efficiently. System development methods involve hardware and software design steps, component integration testing, and system performance evaluation. Soil moisture sensors are used to accurately measure soil moisture as well as to detect soil moisture and automatically activate watering only when needed, while the ESP32 microcontroller module acts as the brain of the system that connects the soil moisture sensor with the Telegram app via a Wi-Fi network. Telegram chat app is used as an intuitive user interface to monitor and control the garden watering system. Through this integration, users can monitor and control the garden watering process practically and effectively. Therefore, Garden Warden has the potential to support modern agriculture by increasing water use efficiency and optimal plant growth.